OPTIMASI SISTEM PENCELUP KAIN BATIK PADA PROSES PEMBUATAN BATIK - , Wilibrordus Dhaneswara, Dr. Ing. Kusnanto ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Batik is the nation's cultural heritage of Indonesia. Batik is in great demand by the market both local and foreign markets. The process of making batik is done traditionally, especially in the coloring process. This coloring is still done manually by immersion. Dyeing process is repeated until the desired color is obtained. To speed up the coloring process of batik cloth, the writer tries to design batik fabric dyeing equipment. Form of experimental research, which aims to plan and design a batik cloth dyeing equipment and increase the output capacity of the dyeing stage in the process of making batik fabric dyeing equipment. The results showed that the results of design tools to accelerate the dyeing batik cloth batik cloth coloring process, up to 30 minutes per sheet of cloth. In addition, the use of batik cloth dyers, can increase the output capacity of the stage in the process of making batik dyeing, from 5 pieces per day for 8 pieces per day. Use of this equipment dyeing batik cloth, batik industry to increase profitability, from Rp.38.800.000, 00 per month to Rp.62.617.488, 00 per month.